2019
DOI: 10.18502/irjnm.v27i1.973
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of nuclear medicine staff towards radiation protection

Abstract: Introduction: Ionizing radiation in medical imaging is one of the dominant sources of exposure, and correct knowledge of radiation protection, affects staff safety behaviors during procedures. This study aimed to assess the radiation protection Knowledge, Attitude and Practice (KAP) amongst nuclear medicine centers' staff in Iran. Methods: To evaluate the level of radiation protection KAP, a validated questionnaire was distributed between 243 participants considering demographic characteristics in different ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The most important method of proper radiation protection principle implementation is education [10]. Today, with the increase in the number of radiology procedures, all healthcare workers exposed to radiology waves should know how these procedures are performed and how they can better protect themselves [11,12]. The extent of awareness of the healthcare workforce about radiation protection has a considerable impact on the proper attitude and performance regarding protection against radiology waves [13].…”
Section: Introductionmentioning
confidence: 99%
“…The most important method of proper radiation protection principle implementation is education [10]. Today, with the increase in the number of radiology procedures, all healthcare workers exposed to radiology waves should know how these procedures are performed and how they can better protect themselves [11,12]. The extent of awareness of the healthcare workforce about radiation protection has a considerable impact on the proper attitude and performance regarding protection against radiology waves [13].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the effect of previous experience on misconceptions, in their study, Seifi et al, after dividing employees into two categories, one with work experience of up to 15 years and the other with more than 15 years of experience, found that employees with up to 15 years of experience had less knowledge of the undesirable effects of radiation and this probably led to misconceptions [52]. This finding is consistent with earlier research by Mohiri et al, according to which employees with less work experience had correspondingly less knowledge of the undesirable effects of radiation [53].…”
Section: Discussionmentioning
confidence: 97%
“…More specifically, obtaining a higher education degree creates a feeling of self-confidence, personal development, self-realization, and success at work. Combining these factors, the staff acquires better professional satisfaction, an essential ingredient for providing quality health services [52].…”
Section: Discussionmentioning
confidence: 99%